Bead-Selected Antitumor Genetic Cell Vaccines - Herrero Mj; R Botella; R Algás; FM Marco; Aliño Sf (Clinical Medicine Insights: Oncology, 2008)
Cancer vaccines have always been in the scope of gene therapy research. One of the most successful approaches has been working with genetically modified tumor cells. However, to become a clinical reality, tumor cells must suffer a long and risky process from the extraction from the patient to the reimplantation as a vaccine. In this work, we explain our group's approach to reduce the cell number required to achieve an immune response against a melanoma murine model, employing bead-selected B16 tumor cells expressing GM-CSF and B7.2.